The Impact of Service Quality and Satisfaction on Customer Loyalty at AFZL Barber Shop - Ruswandi, Jose; Irsandi; Sakti, Trenggono; Asfarani, Suci (Journal of Business and Halal Industry, 2025)
The rapidly growing barber shop industry has heightened competition, making understanding the factors influencing customer loyalty crucial. This study explored the impact of service quality and customer satisfaction on customer loyalty at AFZL Barber Shop in Sukarame, Bandar Lampung. Using a quantitative approach, the research surveyed 109 respondents and analyzed the data through descriptive analysis, validity and reliability tests, and multiple regression analysis. The results showed that service quality and customer satisfaction significantly positively affect customer loyalty. Higher service quality and customer satisfaction levels lead to stronger customer loyalty. The study concludes that businesses must improve service quality and customer satisfaction to maintain customer loyalty in a competitive market.